2018
DOI: 10.1111/xen.12387
|View full text |Cite
|
Sign up to set email alerts
|

Pigs expressing the human inhibitory ligand PD‐L1 (CD 274) provide a new source of xenogeneic cells and tissues with low immunogenic properties

Abstract: These data indicate a low immunogenic, immune-protected status of cells from hPD-L1 transgenic pigs. The integration of the hPD-L1 concept into existing multi-transgenic pigs is promising to achieve long-term survival of porcine xenografts in non-human primate recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 70 publications
1
29
0
1
Order By: Relevance
“…Although there are many other genetic manipulations that could be considered, some of which are aimed to protect against the human adaptive immune response, for example, swine leukocyte antigen (SLA) class I‐knockout, SLA class II knockdown, transgenic expression of cytotoxic T lymphocyte‐associated protein 4‐immunoglobulin (CTLA4‐Ig) or programmed cell death‐ligand 1 (PD‐L1), our opinion is that, although they are likely to be beneficial, they are not as important at this early stage in the development of xenotransplantation as manipulations that protect against the innate immune response. Although they will be advantageous in the near future, at present there are immunosuppressive agents (admittedly not all yet approved by national regulatory authorities) that can effectively prevent the adaptive response, for example, anti‐CD40 monoclonal antibodies (mAbs) .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many other genetic manipulations that could be considered, some of which are aimed to protect against the human adaptive immune response, for example, swine leukocyte antigen (SLA) class I‐knockout, SLA class II knockdown, transgenic expression of cytotoxic T lymphocyte‐associated protein 4‐immunoglobulin (CTLA4‐Ig) or programmed cell death‐ligand 1 (PD‐L1), our opinion is that, although they are likely to be beneficial, they are not as important at this early stage in the development of xenotransplantation as manipulations that protect against the innate immune response. Although they will be advantageous in the near future, at present there are immunosuppressive agents (admittedly not all yet approved by national regulatory authorities) that can effectively prevent the adaptive response, for example, anti‐CD40 monoclonal antibodies (mAbs) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, further genetic modifications are needed to increase long‐term graft survival and reduce immunosuppressive treatments. Especially, concepts to decrease cellular immune responses are now coming into focus as they are thought to reduce immune suppressive regimes to clinical applicable levels …”
Section: Discussionmentioning
confidence: 99%
“…Porcine peripheral blood mononuclear cells (PBMC) from piglet 7070 F3 were isolated and cultivated as previously described . For maintaining cells in culture for up to 13 days, 2 µg/mL concanavalin A (Sigma‐Aldrich) and 100 ng/mL rhIL‐2 (ImmunoTools) were added to the culture.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that human PD-L1 expression protects pig fibroblasts from human CTL and NK cell cytotoxicity. This protection is increasable by tumor necrosis factor-α (TNF-α)-induced PD-L1 upregulation (Buermann et al, 2018).…”
Section: Pd-l1 Expression On Donor Cells Renders Them Somewhat Lowmentioning
confidence: 99%
“…It has been shown that human PD‐L1 expression protects pig fibroblasts from human CTL and NK cell cytotoxicity. This protection is increasable by tumor necrosis factor‐α (TNF‐α)‐induced PD‐L1 upregulation (Buermann et al, ). Similar results were obtained by Plege‐Fleck et al () in the case of a pig to rat xenotransplantation.…”
Section: Introductionmentioning
confidence: 99%